2012
DOI: 10.1016/j.molcel.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The Histone H2B Monoubiquitination Regulatory Pathway Is Required for Differentiation of Multipotent Stem Cells

Abstract: Extensive changes in posttranslational histone modifications accompany the rewiring of the transcriptional program during stem cell differentiation. However, the mechanisms controlling the changes in specific chromatin modifications and their function during differentiation remain only poorly understood. We show that histone H2B monoubiquitination (H2Bub1) significantly increases during differentiation of human mesenchymal stem cells (hMSCs) and various lineage-committed precursor cells and in diverse organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 36 publications
16
134
0
Order By: Relevance
“…During the revision of our manuscript, two reports were published in Mol Cell [14,15]. They show similar results to our data and support our conclusion significantly.…”
Section: Dear Editorsupporting
confidence: 90%
“…During the revision of our manuscript, two reports were published in Mol Cell [14,15]. They show similar results to our data and support our conclusion significantly.…”
Section: Dear Editorsupporting
confidence: 90%
“…Surprisingly, although H2Bub1 is associated preferentially with transcribed genes and its levels correlate positively with their expression rates , transient knockdown of RNF20 affects only a relatively small fraction of the transcriptome . Other studies showed that while affecting only marginally steady-state transcription, H2Bub1 depletion has a more pronounced impact on inducible transcriptional programs triggered in response to various cues (Fuchs et al 2012;Karpiuk et al 2012;Weiner et al 2012). Moreover, H2Bub1 is preferentially required for transcriptional induction of relatively long genes in response to retinoic acid (Fuchs et al 2012), in agreement with an in vitro study implicating a positive role for H2Bub1 in transcription elongation (Pavri et al 2006).…”
Section: [Supplemental Materials Is Available For This Article]supporting
confidence: 76%
“…Aberrant H2Bub1 levels can affect development (Wright et al 2011), apoptosis (Walter et al 2010), stem cell differentiation (Buszczak et al 2009;Fuchs et al 2012;Karpiuk et al 2012), viral infection outcome (Sarkari et al 2009;Fonseca et al 2012), and cell cycle progression (Hwang and Madhani 2009) and can promote cancer Blank et al 2012;Johnsen 2012;. Several mechanisms have been proposed to underlie the ability of H2Bub1 to exert those diverse effects, including impact on higher-order chromatin organization (Fierz et al 2011), altered nucleosome stability (Chandrasekharan et al 2009), regulation of H2A-H2B dimer displacement (Pavri et al 2006), and modulation of the recruitment of specific factors to chromatin (Shema-Yaacoby et al 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Our initial hypothesis was that H2Bub1 could regulate inducible transcription. This was based on several studies showing that H2Bub1 is important for the regulation of inducible phenotypes like cell differentiation 13 or inflammation. 14 As a model, we used an inducible transcription factor, the estrogen receptor a (ERa), activated as a transcription factor by its cognate ligand 17b-estradiol (E2), and found that H2Bub1 represses the inducible activity of ERa-dependent enhancers.…”
Section: H2bub1 Regulates Inducible Enhancersmentioning
confidence: 99%